Bidens pilosa L.: análises da composição química e atividades biológicas de diferentes populações e condições de cultivo - Delarmelina, Juliana Macedo (2017)
The use of plants for medicinal purposes, for treatment, cure and prevention of diseases, is one of the oldest forms of medicinal practice of mankind. Bidens pilosa L., Asteraceae, popularly called "picão-preto", is a plant traditionally used for the treatment of hepatitis, cancer, diabetes, among other disorders. It is a plant of therapeutic interest because it is rich in chemical compounds associated with human health. However, chemical compounds can vary, qualitatively and quantitatively, according to numerous factors that reflect on their biological activities. Among the main factors that contribute to the chemical variation of plant extracts is the genetic variability, environmental factors and the extraction process, such as the use of solvents with different polarity, for example. Thus, the present study aimed to: a) evaluate the variability of the hydroalcoholic extract and five fractions (hexane, dichloromethane, ethyl acetate, butanol and aqueous), from four populations of B. pilosa (Afonso Claudio, Barra de São Francisco, Cariacica and Muniz Freire), using genetic markers (RAPD), phytochemical analyzes (phytochemical prospecting, ESI (-) FT-ICR MS and total content of flavonoids, tannins and phenolics), analyzes of antioxidant activity in vitro (by DPPH? , ABTS?+ ,, chelating activity on Fe+2 and ß-carotene/linoleic acid assays), and in vivo analyzes to evaluate cytotoxicity, anti-cytotoxicity, mutagenicity and antimutagenicity (by micronucleus test in mouse bone marrow). b) evaluate the variability of hydroalcoholic extract of plants submitted to three growth conditions (organic and inorganic fertilizers and the control) and in different phenological stages (vegetative and flowering), through phytochemical, antioxidant and in vivo analyzes (mutagenicity and cytotoxicity of plants in the flowering stage) and growth. The phytochemical analyzes revealed a significant quantitative and qualitative difference between the samples tested, which reflected in variability in their biological activities (antioxidant, t-test, P<0.5). The results suggest that environmental factors were determinant as compared to genetic factors. In vivo assays demonstrated that the plant did not induce cytotoxicity and mutagenicity in all experimental conditions (Tukey, P <0.5) and was able to protect DNA from damage induced by cyclophosphamide in the anti-cytotoxicity and antimutagenicity assays.